(untitled) (Stato, Chiese e pluralismo confessionale, 2015)
Contributo sottoposto a valutazione SOMMARIO: 1. Il divieto del velo islamico come “proibizione delle proibizioni”. Elementi parzialmente convalidabili nell’interpretazione giuridica – 2. Agar e Khadīja. Due espressioni fondative non strettamente equiparabili – 3. La condizione femminile come criterio guida nell’interpretazione delle diverse consuetudini islamiche – 4. I possibili riflessi della questione di genere sulla comunità politica. Critiche alle impostazioni fondamentalistiche. ABSTRACT: Slavoj Žižek’s reliefs about female conditions in Islamic legal systems This essay tries to analyze a recent Slavoj Žižek’s pamphlet about Islamic law and culture. The Slovenian philosopher intentionally uses an ironical and sardonic style, mixing elements from sociology, literature and psychology. His thoughts still seem not always agreeable, but Slavoj Žižek’s perspective can share some points helpful and useful for a first look at Islamic minorities in Western societies.